Selective Radiologic Imaging in The Diagnosis of Knee Osteoarthritis : a Systematic Literature Review - Yuslila, Ewi; Nadhrati Surura, Hedya; Khairul Fikri, Handy; Mukhlis Wardani, Pitra; Fitria, Mawaddah; Al Bukhari, Al Bukhari (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2025)
This literature study helps clinicians in clinical practice in choosing the right radiological imaging in the diagnosis of Knee Osteoarthritis (KOA) according to the patient's condition. Reference sources were obtained systematically from reputable databases; PubMed, Science Direct, Springer Link, Cochrane Library, and Google Scholar with a range of publication years from 2017 to 2024. The keywords used in this literature searching process are